Development of the theory of boundary-value problems for differential equations in the works by Oleksandr Boichuk (Neliniini Kolyvannya, 2025)
We consider the development of qualitative and constructive methods for investigation of linear, weakly perturbed, and weakly nonlinear boundary-value problems for differential, evolutionary and operator equations in the works by O. A. Boichuk and his disciples.